2016
DOI: 10.1002/adfm.201602600
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Native High‐Density Lipoproteins Inspire Synthesis of Actively Targeted In Vivo siRNA Delivery Vehicles

Abstract: Efficient systemic administration of therapeutic short interfering RNA (siRNA) is challenging. High-density lipoproteins (HDL) are natural in vivo RNA delivery vehicles. Specifically, native HDLs: 1) Load single-stranded RNA; 2) Are anionic, which requires charge reconciliation between the RNA and HDL, and 3) Actively target scavenger receptor type B-1 (SR-B1) to deliver RNA. Emphasizing these particular parameters, we employed templated lipoprotein particles (TLP), mimics of spherical HDLs, and self-assembled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 54 publications
0
50
0
Order By: Relevance
“…http://dx.doi.org/10.1101/247429 doi: bioRxiv preprint first posted online Jan. 12, 2018; We were wondering whether the super toxic TNR-based siRNAs could be used for cancer therapy. We decided to deliver the siRNAs to cancer cells in vivo using templated lipoprotein (TLP) nanoparticles [26].…”
Section: Super Toxic Tnr-derived Sirnas Kill Cells By Targeting Tnr Smentioning
confidence: 99%
See 1 more Smart Citation
“…http://dx.doi.org/10.1101/247429 doi: bioRxiv preprint first posted online Jan. 12, 2018; We were wondering whether the super toxic TNR-based siRNAs could be used for cancer therapy. We decided to deliver the siRNAs to cancer cells in vivo using templated lipoprotein (TLP) nanoparticles [26].…”
Section: Super Toxic Tnr-derived Sirnas Kill Cells By Targeting Tnr Smentioning
confidence: 99%
“…We decided to deliver the siRNAs to cancer cells in vivo using templated lipoprotein (TLP) nanoparticles [26].…”
mentioning
confidence: 99%
“…12 Recently, the co-delivery of chemotherapeutic drugs and siRNA has gained increasing attention owing to enhanced antitumor efficacy over single administration. 13,14 Previous studies showed that simultaneously delivering chemotherapeutic drugs and siRNA via a single targeted vector was more effective in treating some cancers than sequential administration of two separate vectors with one drug in each. 15 This finding indicates that simultaneous delivery of chemotherapeutic drugs and suitable amount of siRNA into the same tumor plays an important role in the cancer treatments.…”
Section: Introductionmentioning
confidence: 99%
“…We first demonstrated that DISE induction works in an in vivo model whereby mice harbor xenografted ovarian cancer cells expressing a CD95L derived shRNA (shL3). We then delivered two siRNAs derived from CD95L (siL2 and siL3) to mice with ovarian cancer xenografts using a nanoparticle platform demonstrated previously to deliver siRNA in vivo [11,12]. Templated lipoprotein particles (TLP) stabilize siRNA and are dependent upon SR-B1 expression for efficient siRNA delivery.…”
Section: Introductionmentioning
confidence: 99%